MOG-IgG in primary and secondary chronic progressive multiple sclerosis: a multicenter study of 200 patients and review of the literature - Jarius, Sven; Haas, Jürgen; Wildemann, Brigitte (Journal of neuroinflammation, 2018)
Antibodies to human full-length myelin oligodendrocyte glycoprotein (MOG-IgG) as detected by new-generation cell-based assays have recently been described in patients presenting with acute demyelinating disease of the central nervous system, including patients previously diagnosed with multiple sclerosis (MS). However, only limited data are available on the relevance of MOG-IgG testing in patients with chronic progressive demyelinating disease. It is unclear if patients with primary progressive MS (PPMS) or secondary progressive MS (SPMS) should routinely be tested for MOG-IgG.